Histological findings of Lasia spinosa extract in Arthritic Model - Kumar, Mrityunjay; Kakoti, Bibhuti Bhushan; Borah, Sudarshana; Mahato, Kabita; Barman, Kamallochan; Das, Bhanita; Bora, Aditya; Kalita, Pallab; Sutnga, Innocent (Asian Journal of Biological and Life Sciences)
Background: Arthritis is a phrase that encompasses more than 100 different medical disorders. Arthritis is a condition in which one or more joints become inflamed. Arthritis causes cartilage to break down. A joint’s cartilage protects it and allows it to move freely. When pressure is applied to the joint, such as when walking, cartilage absorbs the stress. The bones rub together when there isn’t enough cartilage, producing discomfort, swelling (inflammation), and stiffness. Lymphadenopathy, Oedema, ocular inflammation, glaucoma Bursitis, urethritis, tenosynovitis (tendon sheath effusions) (swollen bursa), Diarrhea, Ulcers in the orogenital area. Materials and Methods: Lasia spinosa is a herbal medication with roots in many different traditional medical systems all over the world. Results: In this investigation, histopathology of the synovial joint revealed that Lasia spinosa group therapy reduced vascularity, lymphocytic infiltration, there was no thickening of the synovial membrane and no lymphoid follicles, indicating angiogenesis. Conclusion: This study reveals the histology of synovial joints, treated with the Lasia spinosa that reduced the vascularity, lymphocytic infiltration, and angiogenesis without causing the synovial membrane to thicken. Our research findings indicated that Lasia spinosa has potent anti-arthritic properties.
Keywords: Arthritis; Freund’s adjuvant; histopathology; Lasia spinosa